Analisis Pengaruh Human Capital dan Efisiensi Biaya terhadap Profitabilitas Perusahaan melalui Kinerja Keuangan - Suginam; Dewi Sarifah Tullah; Azwansyah Habibie; Rizky Indra Saputra (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of Human Capital and Cost Efficiency on Corporate Profitability through Financial Performance as an intervening variable. The research employed a quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The research objects consisted of companies listed on the Indonesia Stock Exchange with a total of 25 company respondents. The results indicated that Human Capital had a positive and significant effect on Financial Performance with a coefficient value of 0.651, while Cost Efficiency had a positive effect of 0.582 on Financial Performance. Furthermore, Financial Performance was proven to have a significant effect on Profitability with a coefficient value of 0.721. The mediation effect test results demonstrated that Financial Performance significantly mediated the relationship between Human Capital and Cost Efficiency on Profitability. In addition, the model evaluation results showed that all research indicators were declared valid and reliable based on loading factor, AVE, Composite Reliability, and Cronbach’s Alpha values that met SEM-PLS standards. This study indicates that improving the quality of human resources and operational cost efficiency can enhance corporate financial performance, which subsequently impacts sustainable profitability improvement.